Zadania.info
Największy internetowy zbiór zadań z matematyki
cornersUpL
cornersUpR

Zadania

Na skróty

Recenzje

Linki sponsorowane

cornersM

Linki sponsorowane

cornersR
Zadanie nr 6055594

Dla x ∈ R ∖ {− 3,− 2,3} wyrażenie -----1---- --2- (x−3)(x+2) − x2−9 jest równe
A) ---−x−-1--- (x2−9)(x+2) B) ---−x+-7--- (x2−9)(x+ 2) C) (x2−x9+)1(x+-2) D) (x2−−29x)−(3x+-2)

Wersja PDF
Rozwiązanie

Ponieważ  2 x − 9 = (x − 3)(x + 3) , wspólnym mianownikiem dwóch danych ułamków jest:

(x− 3)(x + 2)(x + 3) = (x 2 − 9 )(x + 2).

Mamy zatem

-------1-------− --2----= --------(x+--3)------- − ----2(x+--2)----= (x − 3)(x + 2) x2 − 9 (x − 3 )(x+ 2)(x+ 3) (x2 − 9)(x + 2) x + 3− 2x − 4 −x − 1 = ---2------------ = ---2------------. (x − 9 )(x + 2) (x − 9)(x + 2 )

 
Odpowiedź: A

Wersja PDF